Shopping behind the seams judging quality in clothes - Learning Seed Company ([Chicago, Ill.] : Learning Seed, 2009)
This program show viewers how to spot well-made clothes, how to test clothes before buying, and what quality seams, hems and pockets look like. viewers will learn the four questions to ask before buying clothes, and how to evaluate a garment's fabric and lining
Teaching guide available at www.learningseed.com
Title from title screen
DVD Format
With English subtitle
Keywords: Clothing and dress -- Purchasing; Shopping; Consumer education